Generalized de Rham – Hodge complexes, the related characteristic Chern classes and some applications to integrable multidimensional differential systems on Riemannian manifolds - Bogolubov, N.N.; Prykarpatsky, A.K. (Український математичний журнал, 2007)
The differential-geometric aspects of generalized de Rham – Hodge complexes naturally related with integrable
multidimensional differential systems of M. Gromov type, as well as the geometric structure of Chern characteristic classes are studied. Special differential invariants of the Chern type are constructed, their importance for the
integrability of multidimensional nonlinear differential systems on Riemannian manifolds is discussed. An example of the three-dimensional Davey – Stewartson type nonlinear integrable differential system is considered,
its Cartan type connection mapping and related Chern type differential invariants are analized. Досліджено диференціально-геометричні аспекти узагальнених комплексів де Рама-Ходжа, що природним чином пов'язані з інтегровними багатовимірними диференціальними системами типу M. Громова, а також геометричну структуру характеристичних класів Черна. Побудовано спеціальні диференціальні інваріанти типу Черна та розглянуто їх важливість для інтегровності багатовимірних нелінійних диференціальних систем на ріманових многовидах. Розглянуто приклад тривимірної нелінійної інтегровної диференціальної системи типу Деві-Стюартсона і проаналізовано їх сполучне відображення та споріднені диференціальні інваріанти типу Черна.